First record of Stenoheriades Cockerell in tropical Asia: Stenoheriades bifida, new species (Hymenoptera: Megachilidae) - Griswold, Terry (Zootaxa, 2018)
The little known osmiine genus Stenoheriades Cockerell, previously thought to be restricted to the Afrotropics, the Mediterranean region, and the Arabian Peninsula, is here recorded from tropical Asia in the form of S. bifida, new species. This disjunct distribution adds to a growing list of endemic megachilids in southern India. The new species exhibits novel morphologies in the Megachilidae that also distinguish it from previously known species groups in Stenoheriades.